LINGUISTIC FACTORS IN CHANGING MEANING OF IDIOMATIC COMPOUNDS IN ENGLISH AND UZBEK LANGUAGES - Odinaxon TEMIROVA (TADQIQOTLAR, 2026)
Annotation This article explores the linguistic factors that contribute to changes in the meanings of idiomatic compounds in English and Uzbek languages. Idiomatic compounds — fixed multi-word expressions whose overall meaning cannot be deduced from the meanings of individual components — are deeply rooted in cultural and historical contexts. The research focuses on semantic shifts, influence of cultural contact, translation challenges, and cognitive motivations behind idiom evolution. Drawing on comparative analysis, the paper examines how social changes, language contact, metaphorical extensions, and communicative needs affect idiomatic usage and interpretation in both languages. It highlights key differences and similarities between English and Uzbek idioms, reflecting distinct cultural values, worldview patterns, and linguistic structures. Additionally, the study discusses how globalization and increased bilingualism influence idiomatic transformation. The findings show that semantic adaptation often involves metaphorical reconceptualization, pragmatic reanalysis, and idiom borrowing or calquing. This article contributes to cross-linguistic idiom studies and provides insights for translators, language teachers, and computational linguists dealing with natural language understanding. The comparative framework demonstrates that while some idiomatic changes are universal, others are language- specific, driven by sociocultural dynamics.